Penyuluhan Good Manufacturing Practices (GMP) Marning Jagung di Desa Kertosari Kecamatan Arjasa Kabupaten Situbondo - Gema Iftitah A. Yekti; Sulistyaningsih; Supatra (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Kertosari Village is one of the centers for “marning” corn-processed products in Situbondo. Until now there are three corn-marketing UKMs in Kertosari Village whose products are marketed outside the city, such as Banyuwangi, Malang, to Jakarta. However, so far UKMs have not implemented GMP in their production processes and tend to use makeshift production rooms with simple tools. Thus, food safety, competitiveness, and product quality are still not a priority for UKMs. The layout of the production process is not by following under GMP principles. This happened because of their limited knowledge and skills regarding GMP principles. Therefore, an extension on the application of GMP principles needs to be done to improve product quality and safety. In addition, GMP principles can also guarantee the health and safety of workers. An extension on the application of GMP principles was carried out using the focus group discussion (FGD) method. The material presented includes the concept of food safety, contamination related to processed food production, and GMP principles. The results of the extension show an increase in knowledge by 25%.